Glossopharyngeal neurinoma of incidental finding in a 65-year-old female patient: case report - Kantenga Dieu Merci Kabulo; Kazuhito Takeuchi; Yasuo Yamada; Afsal Sharafundeen; Kazadi Kaluile Ntenga Kalangu; Yoko Kato (Egyptian Journal of Neurosurgery, 2023)
Abstract Background The glossopharyngeal nerve is both a sensitive and motor entity that emerges from the posterior lateral sulcus of the bulb and exits the skull through the jugular foramen. Schwannomas arising from glossopharyngeal nerves are extremely rare, and the clinical and imaging features of glossopharyngeal schwannomas closely resemble that of acoustic schwannomas. Case presentation We report a case of a 65-year-old female patient with glossopharyngeal neurinoma of incidental finding on brain CT scan requested after she sustained a minor traumatic brain injury. She was taken to the operating room, and the tumor was excised endoscopically via a retrosigmoid approach and the postoperative course was simple and uneventful. Histopathology of the sample showed short spindle-shaped cells with poor atypia proliferated in fascicles, and shelf-like arrangement of nuclei was seen partially, which was in keeping with a neurinoma. Conclusions Glossopharyngeal neurinoma may not present with obvious symptoms and signs related to its compression and may also be found incidentally compared to its counterpart vestibular schwannoma.